A Comparative Study of the Body Composition of Male and Female Students of Rural and Urban Area (International Journal of Food and Nutritional Sciences, 2022)
The purpose of this research study was a Comparative Study of the Body Composition of Male and Female Students of Rural and Urban Area. In this research study, the students of the rural and the urban schools of Sabarkantha district were selected as the samples, In this research study the students studying in standard 8, 9 and 10 were selected. In this research study, the boys and the girls students of the rural and urban schools of Sabarkantha district were selected. In this research study 200 male students and 200 female students total 800 samples were selected. In this research study the students between the age group 13 to 18 were selected. In the scale of measurement, the weight was measured with a weighing fork. Height was measured using a tape measure and body mass index was measured using a formula. In order to compare physical structure of male and female students of rural and urban area: “t” test was applied and relevance was checked at the level of 0.05 level. There was no significant difference in the weight, height and body mass index of the urban and rural boys. It can be said that the weight of both the groups was similar.